The English Reading Habits of English Language Education Undergraduate Students at English Department - Windha Aestetika Wulandari; Utari Praba Astuti; Furaidah Furaidah (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Good reading habits help comprehension and logic because they can empower to absorb material analytically, critically, and reflectively. However, the technique for encouraging an interest in reading, particularly in schools and universities, has not obtained the best outcomes. In this case, family, community, and educational institutions simultaneously play a significant role in promoting English Foreign Language students' enthusiasm for reading. Therefore, the aim of this study is to determine how ELE undergraduate students reading habits in English Department, Universitas Negeri Malang. This type of research used descriptive qualitative. The data collection technique used was a questionnaire form and distributed via Google form. The questionnaire discussed students' attitudes towards reading, purpose of reading, reading frequency, and reading preferences. The results showed that most of the ELE undergraduate students have high reading habit. However, students’ reading habits still need to be improved. It is shown that the students like reading as an indispensable part of their lives because of the reading treatment they get from an early stage of age. It makes them have a positive attitude towards reading, they also have a purpose for reading, and increase their reading preferences. Furthermore, they also need to increase their frequency of reading practice and the number of books read. Keywords: reading habits, English Language Education (ELE), English Department Abstrak: Kebiasaan membaca yang baik dapat membantu pemahaman dan logika karena dapat memudahkan untuk menerima materi secara analitis, kritis, dan reflektif. Namun, teknik yang digunakan untuk mendorong minat membaca, khususnya di sekolah dan universitas, masih belum mendapatkan hasil yang terbaik. Dalam hal ini, keluarga, masyarakat, dan lembaga pendidikan secara bersamaan memiliki peran penting dalam mendorong minat membaca Bahasa Inggris siswa. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui bagaimana kebiasaan membaca mahasiswa Jurusan Bahasa Inggris Universitas Negeri Malang. Jenis penelitian yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah kuesioner dan disebarluaskan melalui google form. Kuesioner tersebut membahas sikap siswa terhadap membaca, tujuan membaca, frekuensi membaca, dan preferensi membaca. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa juusan pendidikan Bahasa Inggris memiliki kebiasaan membaca yang tinggi. Namun, kebiasaan membaca siswa masih perlu ditingkatkan lagi. Terlihat bahwa siswa menyukai membaca, karena sebagai bagian yang tak terpisahkan dari kehidupan karena mereka telah dilatih membaca sejak usia dini. Oleh karena itu, mereka memiliki sikap positif terhadap membaca, mereka juga memiliki tujuan untuk membaca, dan meningkatkan preferensi membaca mereka. Selain itu, mereka juga perlu meningkatkan frekuensi latihan membaca dan jumlah buku yang dibaca. Kata kunci: kebiasaan membaca, Pendidikan Bahasa Inggris, Jurusan Sastra Inggris